Melatonin Lowers HIF-1α Content in Human Proximal Tubular Cells (HK-2) Due to Preventing Its Deacetylation by Sirtuin 1 - Owczarek, Aleksandra; Gieczewska, Katarzyna B.; Polanska, Marta; Paterczyk, Bohdan; Gruza, Andrzej; Winiarska, Katarzyna (Frontiers in Physiology, 2021)
Although melatonin is widely known for its nephroprotective properties, there are no reports clearly pointing at its impact on the activity of hypoxia-inducible factor-1 (HIF-1), the main mediator of metabolic responses to hypoxia, in kidneys. The aim of the present study was to elucidate how melatonin affects the expression of the regulatory subunit HIF-1α in renal proximal tubules. HK-2 cells, immortalized human proximal tubular cells, were cultured under hypoxic conditions (1% O2). Melatonin was applied at 100 μM concentration. Protein and mRNA contents were determined by Western blot and RT-qPCR, respectively. HIF-1α acetylation level was established by means of immunoprecipitation followed by Western blot. Melatonin receptors MT1 and MT2 localization in HK-2 cells was visualized using immunofluorescence confocal analysis. It was found that melatonin in HK-2 cells: 1) lowered HIF-1α protein, but not mRNA, content; 2) attenuated expression of HIF-1 target genes; 3) increased HIF-1α acetylation level; 4) diminished sirtuin 1 expression (protein and mRNA). Sirtuin 1 involvement in the regulation of HIF-1α level was confirmed applying cells with silenced Sirt1 gene. Moreover, the presence of MT1 and MT2 receptors was identified in HK-2 cells and their ligand, ramelteon, turned out to mimic melatonin action on both HIF-1α and sirtuin 1 levels. Thus, it is concluded that the mechanism of melatonin-evoked decline in HIF-1α content involves increased acetylation of this subunit which results from the attenuated expression of sirtuin 1, an enzyme reported to deacetylate HIF-1α. This observation provides a new insight to the understanding of melatonin action in kidneys.